The Orthography and Dating of Simonas Daukantas’s Unfinished Second Collection of Song Bundles - Subačius, Giedrius (Senoji Lietuvos literatūra, 2024)
Simonas Daukantas collected Lithuanian folk songs for almost his entire creative life (at least 1827–1861). He published his first collection of songs in 1846 (DAJNES Żiamajtiû pagał Ƶôdiû Dajnĩnikû ĩszraszytas, Petropĩlie: Spaudinie pas C. Kray) and was preparing the second one, but did not complete it. This article mostly deals with the orthography and dating of the three bundles of songs (XXIV, XXX, and XXX) that were intended for this second collection. It also elaborates on the time Daukantas completed his hand copy of Simonas Stanevičius song edition of 1829 (DAYNAS ŻEMAYCZIU SURYNKTAS YR YSŹDUTAS PAR SYMONA STANEWICZE Mokslynyka Lyteraturas yr Grażiuju Prytirymu. WYLNIUJE. SPAUSTUWIEJ’ B. NEUMANA) and edited the orthography of his own handwritten songs.One song, “It Is Hard to our Little Neighbor” (“Mūsų susiedeliui vargas yra”; XXIV bundle f. 33v), may be considered originating in the somewhat earlier period, in the last years of Daukantas residing in St Petersburg (…–1850). Its most palpable orthographic features: [an, ọn], [ọ], possibly .During Varniai period (1850–1855) Daukantas must have written down several songs: “For that One Night” (“Dėl tos vienos nakties”) with the names of winds and a proverb (XXIV bundle f. 30r); three songs (XXIV bundle f. 30r); and the song “(He) Sings Alone” (“Vienas dainuoja”; XXIV bundle f. 32r). Graphochronologically significant orthographic features: ; praet. 3; [ą] in word‑initial and word‑medial positions.During the Kálnėnai period (1859–1861), Daukantas possibly wrote down most of the songs he intended for his second collection of folk songs—those were the major texts of the bundles XXIV (f. 2r–29r), XXX (f. 1r–12v), and XXXI (f. 1r–18v). Their most salient orthographic features were: praet. 3; [ą] in word‑initial and word‑medial positions; (also often older apostrophic forms: in iness. sg. [f.] case; ). Somewhat later, but still, in Kálnėnai, Daukantas must have copied a book of Lithuanian songs by Simonas Stanevičius (StDƵn, 1829) in his own hand. The newer orthographic features dominate this copy: non‑apostrophic iness. sg. (f.) () and ().During Papilė period (1861–1864), Daukantas probably wrote down one song, “The More Seldom I Sowed” (“Juo retai sėjau”; XXIV bundle f. 33r), and both added footnotes and corrected the texts in the XXX bundle. Palpable orthographic features were: iness. sg. (f.); ; ultimately the newest latest corrections clearly visible there: → praet. 3; → gen. sg. m. Analogous corrections of → must have been occasionally made in XXXI f. 4v and StDƵn 18 also during the Papilė period.
Keywords: 19 c. Lithuanian folk songs; Simonas Daukantas; History of Lithuanian orthography; graphochronology; dating by orthography